PENGARUH DAMPAK PENINGKATAN RUAS JALAN ANTARA KABUPATEN BIAK NUMFOR – KABUPATEN SUPYORI TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN SUPYORI, PAPUA - eli wanggai; Risky Novan Ngutra; Apolo Safanpo (Magister Perencanaan Wilayah dan Kota Universitas Cenderawasih, 2021)
The system of transportation infrastructure and facilities as a basis is a requirement for regional economic movement, where as a support system and a driving force for transportation infrastructure is very wary of the efficiency and effectiveness of regional economic activities, production, food distribution, industry, export/trade, tourism, agro-industry and business. will have an impact on the economic growth of a region/rural area. The purpose of this paper is to identify how big the impact and will affect improving the quality of roads on regional development and economic growth in Supyori district. The problem in this paper is that the contribution of improving the quality of roads has not been identified on the development of the Mimika Regency area, research or study efforts that explain how big the impact is after the quality of the roads is improved.